Finite element analysis of thermal-induced reflective cracking in composite pavement with mitigation strategies. (1st May 2022) - Xie, Pengyu; Wang, Hao
Highlights: Developed finite element (FE) models to simulate thermal-induced reflective cracking. Analyzed crack initiation and propagation using stress-based fatigue model and modified Paris' law. Compared two mitigation strategies, namely thicker asphalt overlay and stress absorbing interlayer. Abstract: The cyclic temperature variation causes contraction and curling of concrete slabs, which results in thermal-induced reflective cracking in asphalt overlay. This study developed finite element (FE) models to analyze thermal-induced reflective cracking in composite pavement and evaluate the effectiveness of mitigation strategies. The FE models were first developed to simulate the indoor full-scale test in which the concrete slab moved horizontally at the controlled displacement rate. Crack initiation and propagation phases were characterized using stress-based fatigue model and the modified Paris' law with J-integral, respectively. The developed FE model was found able to capture the mechanism of thermal-induced reflective cracking and provide mechanical responses for crack analysis. After that, the FE models were developed for reflective cracking under cyclic thermal loading due to field temperature variation and two mitigation strategies were analyzed, increasing overlay thickness and applying stress absorbing interlayer. As asphalt overlay thickness increases, the cycles for crack initiation and propagation increase, but the effectiveness decreases after certain thickness. On the other hand, stress absorbing interlayer alleviates the critical stress caused by the movement of concrete joint. The stress-absorbing interlayer shows better cost-effectiveness in mitigation of thermal-induced reflective cracking, which should be further evaluated for traffic-induced reflective cracking.